2023
DOI: 10.1002/cbic.202200580
|View full text |Cite
|
Sign up to set email alerts
|

Designer, Programmable DNA‐peptide hybrid materials with emergent properties to probe and modulate biological systems

Abstract: The chemistry of DNA endows it with certain functional properties that facilitate the generation of self-assembled nanostructures, offering precise control over their geometry and morphology, that can be exploited for advanced biological applications. Despite the structural promise of these materials, their applications are limited owing to lack of functional capability to interact favourably with biological systems, which has been achieved by functional proteins or peptides. Herein, we outline a strategy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 160 publications
0
4
0
Order By: Relevance
“…Peptide-DNA hybrid nanotechnology could also generate new classes of articial extracellular matrices. 203 It has…”
Section: Future Prospects Of Dna Nanotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…Peptide-DNA hybrid nanotechnology could also generate new classes of articial extracellular matrices. 203 It has…”
Section: Future Prospects Of Dna Nanotechnologymentioning
confidence: 99%
“…Peptide-DNA hybrid nanotechnology could also generate new classes of artificial extracellular matrices. 203 It has recently been shown that ex vivo cellular scaffolding on which human cervical cancer cells attach robustly, live, and survive with high migration rates, may be produced using the combination of peptide and DNA nanotechnology.…”
Section: Future Prospects Of Dna Nanotechnologymentioning
confidence: 99%
“…adhesive receptor ligands) along their surface in defined positions and densities with nanometer precision that can provide ways to control cell behaviors [ 79 ]. They also can be combined with peptides to create 3D hybrid scaffold materials for various medical applications, including tissue regeneration [ 80 ]. Interestingly, tensegrity principles are often used to design these self assembled DNAs to produce stable 3D structures and desired mechanical responsiveness [ 81 , 82 ].…”
Section: Mechanobiology and Mechanotherapeuticsmentioning
confidence: 99%
“…DNA-based hybrid materials constructed by combining DNA with other materials, such as polymers, metallic nanoparticles, peptides, and inorganic compounds, have attracted significant attention in the field of biological engineering. [22][23][24] Combining DNA with other materials confers additional functionalities to the already large repertoire of capabilities that DNA demonstrates. [25][26][27] The advancement of DNA nanotechnology and the limitless possibility to combine DNA with a wide array of functional materials have opened a broad and innovative area of research toward developing novel multi-functional DNA-based hybrid materials.…”
Section: Introductionmentioning
confidence: 99%